Microbial Spectrum and Antibacterial Susceptibility of Endophthalmitis Cultures in a Tertiary Referral Center in the Midwestern United States: An Analysis From 295 Patients. (May 2021) - Gemayel, Michael; Neiweem, Ashley; Aebi, Brent; Bracha, Peter; Ciulla, Thomas
Purpose: This work evaluates the microbial spectrum and antibiotic susceptibility pattern of endophthalmitis cases in a large tertiary referral center in the Midwestern United States. Methods: This retrospective case series included patients with clinically diagnosed endophthalmitis between April 14, 2006 and April 14, 2016, in whom ocular samples were submitted to the Microbiology Department at Indiana University. The patients were assessed by 11 vitreoretinal surgeons from 6 different sites in Indianapolis, including Indiana University and private practices, who receive patients from urban, suburban, and rural agricultural areas. Submitted specimens were cultured with the following media: blood agar, chocolate agar, MacConkey agar, and thioglycolate broth. Results: A total of 327 specimens from 295 patients were analyzed, with 96 (32.5%) samples from 90 (30.5%) patients meeting the criteria of confirmed growth. Of these 96 positive specimens, 83 (86.5%) organisms were identified as bacterial, and 13 (13.5%) were identified as fungal. Coagulase-negative Staphylococcus was the most common isolate (37.5%). Fifty gram-positive isolates and 10 gram-negative isolates underwent susceptibility testing. All 40 of the gram-positive isolates tested for vancomycin sensitivity were susceptible, whereas all 7 of the gram-negative isolates tested for ceftazidime sensitivity were susceptible. Conclusions: Empiric treatment with vancomycin and ceftazidime remains appropriate in most cases of endophthalmitis in the Midwestern United States, with 100% susceptibility of bacterial organisms tested with these antibiotics in this series. The high fungal culture rates in this study highlight the utility of obtaining vitreous cultures and potential need for antifungal agents in suspicious cases.